Implementasi E-Government Dalam Transformasi Pelayanan Publik: Suatu Tinjauan Literatur - Muhammad Farhan Merdwinsyah; Melati Jafari; Alfindo Ananta; Boni Saputra; M. Fachri Adnan (CV. ITTC INDONESIA, 2026)
This study aims to analyze the implementation of e-government in the transformation of public services in Indonesia through a systematic literature review approach. Using the narrative review method, this study examines 20 selected academic journals from 2020 to 2026, sourced from Scopus-indexed, SINTA-indexed, and reputable international databases. The findings reveal that e-government implementation significantly accelerates service delivery, enhances transparency, accountability, and citizen satisfaction. Key success factors include strong political leadership commitment, digital infrastructure readiness, human resource capacity building, and inter-agency integration. Nevertheless, persistent challenges such as the digital divide, low public digital literacy, uneven infrastructure distribution, and bureaucratic resistance continue to hinder optimal implementation. This study recommends a comprehensive national e-government framework, equitable digital infrastructure investment, public digital literacy programs, and an integrated inter-agency governance platform to achieve a fully transformed public service ecosystem across Indonesia.